CULTURE SHOCK MAHASISWA PENDIDIKAN BAHASA MANDARIN DALAM PROGRAM PERTUKARAN KE NANCHANG (STUDI PENDIDIKAN BAHASA MANDARIN) - Andi Tiara Sikma Tanjung; Misnawaty Usman; Nirdayanti Mustarih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the forms of culture shock experienced and the adaptation strategies employed by Mandarin Language Education students from UNM during an exchange program in Nanchang, China. A qualitative phenomenological method was used, involving 20 informants who participated in in-depth interviews. The results indicate that all informants experienced the four stages of culture shock outlined in Oberg’s (1960) model: honeymoon, frustration/crisis, adjustment, and acceptance. Adaptation strategies included the use of digital media, taking the initiative to build friendships with local students, communicating with family, and adjusting learning styles to the more intensive Chinese academic system.